Characterization of large and small-plaque variants in the Zika virus clinical isolate ZIKV/Hu/S36/Chiba/2016. Issue 1 (December 2017) - Kato, Fumihiro; Tajima, Shigeru; Nakayama, Eri; Kawai, Yasuhiro; Taniguchi, Satoshi; Shibasaki, Kenichi; Taira, Masakatsu; Maeki, Takahiro; Lim, Chang; Takasaki, Tomohiko; Saijo, Masayuki
Abstract An Asian/American lineage Zika virus (ZIKV) strain ZIKV/Hu/S36/Chiba/2016 formed 2 types in plaque size, large and small. Genomic analysis of the plaque-forming clones obtained from the isolate indicated that the clones forming small plaques commonly had an adenine nucleotide at position 796 (230Gln in the amino acid sequence), while clones forming large plaques had a guanine nucleotide (230Arg ) at the same position, suggesting that this position was associated with the difference in plaque size. Growth kinetics of a large-plaque clone was faster than that of a small-plaque clone in Vero cells. Recombinant ZIKV G796A/rZIKV-MR766, which carries a missense G796A mutation, was produced using an infectious molecular clone of the ZIKV MR766 strain rZIKV-MR766/pMW119-CMVP. The plaque size of the G796A mutant was significantly smaller than that of the parental strain. The G796A mutation clearly reduced the growth rate of the parental virus in Vero cells. Furthermore, the G796A mutation also decreased the virulence of the MR766 strain in IFNAR1 knockout mice. These results indicate that the amino acid variation at position 230 in the viral polyprotein, which is located in the M protein sequence, is a molecular determinant for plaque morphology, growth property, and virulence in mice of ZIKV.